1997
DOI: 10.1074/jbc.272.45.28726
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Human Chemokine Receptors CXCR4

Abstract: Members of the chemokine receptor family CCR5 and CXCR4 have recently been shown to be involved in the entry of human immunodeficiency virus (HIV) into target cells. Here, we investigated the regulation of CXCR4 in rat basophilic leukemia cells (RBL-2H3) stably transfected with wild type (Wt CXCR4) or a cytoplasmic tail deletion mutant (⌬Cyto CXCR4) of CXCR4. The ligand, stromal cell derived factor-1 (SDF-1) stimulated higher G-protein activation, inositol phosphate generation, and a more sustained calcium ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
101
1

Year Published

1998
1998
2004
2004

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 261 publications
(107 citation statements)
references
References 51 publications
5
101
1
Order By: Relevance
“…Upon receptor activation, these carboxyl-terminal serines and threonines are phosphorylated by G protein-related kinases, which allow ␤-arrestin binding and can lead to both G protein uncoupling and internalization by targeting receptors to clathrin-coated pits (8,41). Wild-type-CXCR3 and Tail(Ϫ)-CXCR3 were immunoprecipitated from extracts made from HEK293 cells transiently transfected with plasmids encoding FLAG-tagged versions of these receptors (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Upon receptor activation, these carboxyl-terminal serines and threonines are phosphorylated by G protein-related kinases, which allow ␤-arrestin binding and can lead to both G protein uncoupling and internalization by targeting receptors to clathrin-coated pits (8,41). Wild-type-CXCR3 and Tail(Ϫ)-CXCR3 were immunoprecipitated from extracts made from HEK293 cells transiently transfected with plasmids encoding FLAG-tagged versions of these receptors (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Trafficking of both CXCR4 and CCR5 appears to require the serine/threonine-rich C-tail (21,44). GRKs mediate phosphorylation of agonist-activated receptors on serine and threonine residues (74).…”
Section: Discussionmentioning
confidence: 99%
“…Mutagenesis of CXCR4 and Internalization of Mutant Receptors-The C-tail of CXCR4 has been shown to be required for agonist and PMA-mediated CXCR4 internalization (44). A recent study using mink lung epithelial cells (Mv-1-Lu) showed that Ser-324 and Ser-325 and the dileucine motif at amino acids 328 and 329 appear to be involved in phorbol ester-but not SDF-1␣-mediated CXCR4 internalization (53).…”
Section: Fig 2 Pma-and Rantes-mediated Ccr5 Internalizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Splenocytes from genetically deficient mice and littermate controls were isolated, pooled, and frozen at Ϫ80°C until use. Membranes were prepared and assayed for GTPase activity (10 g of membrane preparations͞assay) as described (18,19) in the presence and absence of murine CXCL12 (1 M).…”
Section: Methodsmentioning
confidence: 99%